Social Media Marketing Activities Role in Creating Loyalty of Islamic Banks in Indonesia - Raden Roro Fosa Sarassina (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
The increasing number of social media users in Indonesia highlights the growing importance of social media in fostering loyalty. Despite this, there is a lack of models available for analyzing the complex relationship between Social Media Marketing Activities (SMMAs) and loyalty and the various mediating variables that impact this relationship. However, the Customer Relationship Quality (CRQ) model has emerged as a promising approach, providing a framework to analyze the impact of SMMAs on loyalty, as well as key mediating variables like trust, satisfaction, and commitment. Despite the strengths of this model, it has not yet explored the direct relationship between SMMAs and loyalty. In response, this study expands on this framework by adding this direct relationship to the model. To collect data, an online survey was used to gather responses from 138 followers of the Facebook and Instagram accounts of the five largest Islamic banks in Indonesia. The resulting data was analyzed using the powerful Structural Equation Modeling (SEM) approach, with the SmartPLS software used to examine the complex relationships between variables.